Predictability and heritability of individual differences in fear learning - Shumake, Jason (Springer Berlin Heidelberg, 2014)
Our objective was to characterize individual differences in fear conditioning and extinction in an outbred rat strain, to test behavioral predictors of these individual differences, and to assess their heritability. We fear-conditioned 100 Long-Evans rats, attempted to extinguish fear the next day, and tested extinction recall on the third day. The distribution of freezing scores after fear conditioning was skewed, with most rats showing substantial freezing; after fear extinction, the distribution was bimodal with most rats showing minimal freezing, but a substantial portion showing maximal freezing. Longer rearing episodes measured prior to conditioning predicted less freezing at the beginning of extinction, but differences in extinction learning were not predicted by any baseline exploratory behaviors. We tested the heritability of extinction differences by breeding rats from the top and bottom 20 % of freezing scores during extinction recall. We then ran the offspring through the same conditioning/extinction procedure, with the addition of recording ultrasonic vocalizations throughout training and testing. Only a minority of rats emitted distress vocalizations during fear acquisition, but the incidence was less frequent in the offspring of good extinguishers than in poor extinguishers or randomly bred controls. The occurrence of distress vocalizations during acquisition predicted higher levels of freezing during fear recall regardless of breeding line, but the relationship between vocalization and freezing was no longer evident following extinction training, at which point freezing levels were influenced only by breeding and not by vocalization. The heritability (h (2)) of extinction recall was estimated at 0.36, consistent with human estimates. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10071-014-0752-1) contains supplementary material, which is available to authorized users.